Critical Discourse Analysis of Mgdalenaf’s Choices on MSMEs during the Covid-19 Pandemic - Hariyanti, Nunik; An Nur, Fitrinanda; Nabilah, Rifdah Ghinah (UI Scholars Hub, 2022)
This study focuses on how the discourse on helping Micro, Small and Medium Enterprises (MSMEs) during the Covid-19 pandemic is shown on the food vlogger Mgdalenaf. MSMEs are in the spotlight because they are an important sector in the Indonesian economy that has been affected by the Covid-19 pandemic. One of the Indonesian food vloggers with almost 4 million followers on the YouTube channel; since the end of 2020, Mgdalenaf has broadcast programs to help MSMEs in the Jabodetabek area. In 2021, Mgdalenaf and the team were trying to reach a wider range of MSMEs affected by the Covid-19 Pandemic in Java-Bali. MSMEs themselves are the pillars of the Indonesian economy because 60% of Indonesia’s GDP comes from MSMEs. Discourse to help MSMEs through its broadcasts. The researcher aims to reveal the critical discourse raised by the creator of the food vlogger Mgdalenaf related to the issue of helping MSMEs using van Dijk’s critical discourse analysis through three components of analysis, namely text, social cognition and social analysis. The results of this study, the text describes the experiences of SMEs amid the Covid-19 Pandemic. In the context of social cognition, creators have a role to play in helping the affected MSMEs. While the social analysis raised is the dominance of the existing discourse in society, MSMEs represent the lower middle-class economy, which is currently difficult to carry out the production, distribution and consumption processes. In addition, the discourse that emerged was to revive MSMEs as a driver of the community’s economy, and women were also able to contribute to the economy’s running.